TEORI PENETRASI SOSIAL DALAM HUBUNGAN SUAMI ISTRI YANG MENIKAH MELALUI PROSES TA'ARUF - Naufalia Reskiana Saktika (2021)
SOCIAL PENETRATION THEORY OF MARRIED HUSBAND AND WIFE RELATIONSHIP THROUGH TA'ARUF Naufalia Reskiana Saktika Universitas Pembangunan Nasional Veteran Jakarta naufalia.reskiana28@gmail.com ABSTRAK Ta'aruf is a method of introduction between men and women, which is regulated by signs in accordance with Islamic law. There are limitations that come from an Islamic perspective. Ta'aruf is considered the best solution for finding a life partner. This research focuses on the process of communication development that occurs in husband-wife relationships who are married through the ta'aruf process. This type of research is qualitative. Social Penetration Theory is used to help explain the stages of development of relationships in relationships through communication that exists between ta'aruf pairs. The development of this relationship will result in an expansion from interpersonal communication to family communication, which shows that there is an agreement of symbols and definitions in it according to the Family Communication Theory. The phenomological approach used is used to analyze the experiences of informants who have or are undergoing ta'aruf. Sources of research data come from interviews with informants. The results of this study will show that the ta'aruf process carried out before marriage is positive and negative. The role of the mediator is very important, in this process the mediator becomes an intermediary in the exchange of information between the two. The success and failure of the ta'aruf process is based on the characteristics of interpersonal communication that exists between ta'aruf pairs. The ta'aruf process that occurs is only up to the exploratory orientation and affective stages, this is due to the existence of separate restrictions or signs in the process. The stages that have been taken will determine the continuation of the stages that will be undertaken, namely marriage. Keywords: Interpersonal Communication, Family Communication, Ta'aruf, Social Penetration Theory, Marriage